Circulating levels of CTRP3 in patients with type 2 diabetes mellitus compared to controls: A systematic review and meta-analysis. (November 2020) - Moradi, Nariman; Najafi, Mohammad; Sharma, Tanmay; Fallah, Soudabeh; Koushki, Mehdi; Peterson, Jonathan M.; Meyre, David; Fadaei, Reza
Abstract: Growing evidence suggests that adipokines may be therapeutic targets for cardiometabolic diseases such as type 2 diabetes mellitus (T2DM). C1q TNF Related Protein 3 (CTRP3) is a newly discovered adipokine which shares properties with adiponectin. The literature about the association between circulating levels of CTRP3 and T2DM has been conflicting. The present study reassessed the data on circulating CTRP3 levels in T2DM patients compared to controls through a systematic review and meta-analysis. A literature search was performed in Medline, Embase, Scopus, and Web of science to identify studies that measured circulating CTRP3 levels in T2DM patients and controls. The search identified 124 studies of which 59 were screened for title and abstract and 13 were subsequently screened at the full text stage and 12 studies included into the meta-analysis. Subgroup analyses, depending on the presence of T2DM complications, matching for BMI, age, and cut off value of fasting blood sugar and HOMA-IR, were performed. The results show that circulating CTRP3 levels are negatively associated with T2DM status (SMD: −0.837; 95% CI: (−1.656 to −0.017); p = 0.045). No publication bias was identified using the Begg's rank correlation and Egger's linear regression tests (P = 1 and P = 0.44, respectively). Meta-regression demonstrated significant association between CRTP3 levels with BMI (slope: 0.11; 95% CI: 0.04–0.19; p = 0.001) and sex (slope: −0.07; 95% CI: −0.12 to −0.01; p = 0.008). The present systematic review and meta-analysis evidences a negative association between circulating level of CTRP3 and T2DM status. BMI and sex may modify this association.